PRODUKSI DAN KANDUNGAN NUTRIEN HIJAUAN RUMPUT Pennisetum purpureum cv Mott, DENGAN PEMBERIAN PUPUK ORGANIK CAIR HASIL VERMICOMPOSTING LIMBAH SAPI POTONG - Iin Susilawati; Eulis Tanti Marlina; Deden Zamzam Badruzzaman (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Fertilization is a very important effort for Dwarf Elephant Grass (Pennisetum purpureum cv Mott) to achieve forage production and high nutritional quality following its potential. This research aims to determine the yield of dry matter, crude protein content, and crude fiber of Dwarf Elephant Grass by application of liquid organic fertilizer (LOF) resulting from vermicomposting of beef cattle waste. The research was conducted at the Field Laboratory of Forage Crop, and the Ruminant Animal Nutrition and Feed Chemistry Laboratory, Faculty of Animal Husbandry, Padjadjaran University from January to June 2018. The research method used was the experimental method with a Completely Randomized Design using 3 treatments, namely P1 (5,000 L per Ha), P2 (10,000 L per Ha), and P3 (15,000 L per Ha), and 6 replications. Data were processed by analysis of variance and continued with Duncan's Multiple Range Test. The results showed that giving LOF increased the production, increased the content of crude protein, and decreased the crude fiber content of Dwarf Elephant Grass forage. Giving LOF from vermicomposting beef cattle waste at a dose of 15,000 L per Ha resulted in the highest forage dry matter yield (1,925 kg per Ha), one-time cutting at dry season, and the best nutrient content seen from the crude protein content (13.95%) and crude fiber content (28.53%).